Un vistazo a la Criminología de José Antonio Encinas Franco en los inicios del indigenismo jurídico universitario - Espinoza Coila, Michael (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2020)
The article briefly aims to expose the ideas of the educator, politician and lawyer from Puno José Antonio Encinas regarding the causes of indigenous criminality in Peru, as a product of university legal indigenism and briefly present our opinion on the matter, starting from the beginning of the 20th century in the midst of "leguismo" and ending in the future of Peruvian Criminology of the current century.